Peran Pemasaran Digital dalam Integrasi Influencer di Bank Syariah Mempengaruhi Strategi Promosi yang Inovatif - putri yuanti; Iqbal Fasa, Muhammad (Jurnal Manajemen, Akuntansi dan Logistik (JUMATI), 2024)
The place of digital marketing in influencer integration in Islamic banks plays a key role in enhancing innovative promotional strategies. In the fast-paced digital era, Islamic banks must adapt to technology to stay relevant and competitive. Influencer integration is one of the efficient strategies to increase customer understanding and confidence in Islamic bank products and services. This research shows that creative and engaging digital content, and collaboration with influencers who have influence on the target audience, can increase the attention of potential customers and strengthen customer confidence in Islamic banks. Efficient digital marketing strategies include the use of social media such as Instagram, TikTok, and X to disseminate up-to-date product and service data and campaigns on sharia principles and the advantages of sharia products. Keywords: Digital Marketing, Influencer Integration, Promotion Strategy, Islamic Bank, Marketing Innovation.